2011
DOI: 10.1523/jneurosci.2982-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Gain Field Encoding of the Kinematics of Both Arms in the Internal Model Enables Flexible Bimanual Action

Abstract: Bimanual action requires the neural controller (internal model) for each arm to predictively compensate for mechanical interactions resulting from movement of both that arm and its counterpart on the opposite side of the body. Here, we demonstrate that the brain may accomplish this by constructing the internal model with primitives multiplicatively encoding information from the kinematics of both arms. We had human participants adapt to a novel force field imposed on one arm while both arms were moving in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 47 publications
9
76
1
Order By: Relevance
“…To produce different amounts of force for arbitrary combinations of bimanual movements, the motor system, therefore, needs neural circuits that show nonlinear tuning for bimanual actions (Fig. 6 B ; Yokoi et al 2011). One example would be patches of cortex that responded preferentially to a single specific bimanual combination.…”
Section: Resultsmentioning
confidence: 99%
“…To produce different amounts of force for arbitrary combinations of bimanual movements, the motor system, therefore, needs neural circuits that show nonlinear tuning for bimanual actions (Fig. 6 B ; Yokoi et al 2011). One example would be patches of cortex that responded preferentially to a single specific bimanual combination.…”
Section: Resultsmentioning
confidence: 99%
“…For example, static cues (e.g., color) linked to opposing force fields have very limited ability to reduce interference (Gandolfo et al., 1996, Howard et al., 2013), suggesting that neural activity in relevant motor regions may not be affected by such cues. In contrast other contexts such as different dynamic cues (Cothros et al., 2009, Howard et al., 2012, Howard et al., 2015), concurrent motion of the other arm (Howard et al., 2010, Nozaki et al., 2006, Nozaki and Scott, 2009, Yokoi et al., 2011), lead-ins (Howard et al., 2012, Wainscott et al., 2005), and follow throughs (Howard et al., 2015) often allow substantial learning. We suggest that such situations that act as contexts may simply be ones that lead naturally to different neural states in motor related regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yokoi et al (2011) demonstrated a different way in which a multiplicative gain field accounts for internal representations underlying motor memory. They did not dissociate intrinsic and extrinsic reference frames but were able to uncover a different type of gain-field representation.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, studies of neural encoding in M1 have not investigated a gain-field combination of intrinsic and extrinsic coordinates. A key feature of our current work and the Yokoi et al (2011) study was the dense sampling of the generalization function across combinations of two different features. Intriguingly, several studies of neural activity in M1 that have used analogously dense sampling across combinations of different features appear to provide evidence for gain-field encoding across those features.…”
Section: Discussionmentioning
confidence: 99%